Reparations to Africa: examining the African viewpoint - Lombardo, Anthony Peter (MacSphere, 2004)
This thesis explores African opinion on Western reparations to Africa and investigates the prospects and challenges facing a social movement for African reparations. The findings are based on an analysis of 41 semi-structured interviews conducted with, for the most part, African human rights activists, academics, ambassadors to the USA and three members of the Group of Eminent Persons, mandated to advocate reparations to Africa. Respondents were asked about their personal feelings towards reparations and the "West," and about what shape reparations should take. Key themes from the interviews demonstrated a strong desire for "rehabilitative" reparations beyond merely words of apology or acknowledgement. From these results, concepts from existing reparations theory and frameworks are tested and expanded. An investigation of the advocacy literature demonstrates that advocates for reparations to Africa will face a number of challenges with respect to political opportunities, mobilization and framing for a successful social movement for reparations.
Keywords: Sociology; Sociology; Sociology